1994
DOI: 10.1002/bit.260440302
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic investigation of microbial souring in porous media using microbial consortia from oil reservoirs

Abstract: Microbial souring (H2S production) in porous media was investigated in an anaerobic upflow porous media reactor at 60 degrees C using microbial consortia obtained from oil reservoirs. Multiple carbon sources (formate, acetate, propionate, iso- and n-butyrates) found in reservoir waters as well as sulfate as the electron acceptor was used. Kinetics and rates of souring in the reactor system were analyzed. Higher volumetric substrate consumption rates (organic acids and sulfate) and a higher volumetric H(2)S pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Oil reservoir hydrogen sulfide production (commonly referred to as souring) poses health risks to workers and is estimated to cost the petroleum industry billions of dollars per year (Chen et al, 1994) due to lowered hydrocarbon quality and increased infrastructure maintenance related to corrosion (Gieg et al, 2011). Sulfide-producing microorganisms (SPM) are responsible for much of the sulfides in produced oil and gas fluids, especially after water injection has begun to enhance oil recovery, yet not all reservoirs undergoing secondary recovery produce measurable sulfides.…”
Section: Introductionmentioning
confidence: 99%
“…Oil reservoir hydrogen sulfide production (commonly referred to as souring) poses health risks to workers and is estimated to cost the petroleum industry billions of dollars per year (Chen et al, 1994) due to lowered hydrocarbon quality and increased infrastructure maintenance related to corrosion (Gieg et al, 2011). Sulfide-producing microorganisms (SPM) are responsible for much of the sulfides in produced oil and gas fluids, especially after water injection has begun to enhance oil recovery, yet not all reservoirs undergoing secondary recovery produce measurable sulfides.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of souring and its control with nitrate or nitrite have mostly used VFA or lactate as the electron donor for nitrate and sulfate reduction (15,19,21,33,34,45,46). Only Myhr et al (18) also used an oil-flooded bioreactor.…”
Section: Discussionmentioning
confidence: 99%
“…This implies each reaction has a maximum rate constant, and a half reaction constant for each reactant, making a total of 3 model parameters that need to be specified. As illustrated by Chen et al [22,23], kinetics obtained from batch experiments may differ from those found in a bioreactor for similar systems. We use matching from the bioreactor experiments to assess the appropriate parameter values.…”
Section: Microbial Growth and Metabolite Production Modelmentioning
confidence: 99%